2013
DOI: 10.1002/jctb.4215
|View full text |Cite
|
Sign up to set email alerts
|

Biomethanization from sulfate‐containing municipal solid waste: effect of molybdate on microbial consortium

Abstract: BACKGROUND: The effect of molybdate on a microbial consortium of dry thermophilic anaerobic digestion (AD) from sulfate-containing municipal solid waste was studied. RESULTS:The study showed molybdate inhibition affecting hydrolysis, acidogenesis, and methanogenesis, but the main microbial populations in AD can sustain the molybdate load over a short period of time. Molybdate was not a bactericide for all members of the principal groups, only a few of them are affected. Although all the microbial populations d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The pH level reached a constant value of 7.8 ± 0.4 in all BMP tests. This has been identified as the optimal pH for enhanced acetogenic and methanogenic activity (De la Rubia et al, 2009;Zahedi et al, 2014bZahedi et al, , 2016. At the end of the assay, VFA concentrations were lower than 0.2 g/g VS and no propionic acid was detected under any pre-treatment tested.…”
Section: Effect Of Fna Pre-treatment On the Final Characteristics Of mentioning
confidence: 95%
“…The pH level reached a constant value of 7.8 ± 0.4 in all BMP tests. This has been identified as the optimal pH for enhanced acetogenic and methanogenic activity (De la Rubia et al, 2009;Zahedi et al, 2014bZahedi et al, , 2016. At the end of the assay, VFA concentrations were lower than 0.2 g/g VS and no propionic acid was detected under any pre-treatment tested.…”
Section: Effect Of Fna Pre-treatment On the Final Characteristics Of mentioning
confidence: 95%
“…TS, VS, soluble Kjeldahl nitrogen (SKN) and SCOD were determined according to standard methods [22] and Zahedi et al [23,24]. NH 4 + was analyzed via ion chromatography (ICS5000, DIONEX).…”
Section: Methodsmentioning
confidence: 99%
“…The cellular concentration and percentages of Eubacteria, Archaea, Firmicutes, Clostridium and different groups of methanogens, described below, were obtained by epifluorescence method (FISH). These analyses were performed according to Montero et al (2009) and Zahedi et al (2013aZahedi et al ( , 2013bZahedi et al ( , 2014aZahedi et al ( , 2014b. The 16S rRNA-targeted oligonucleotides employed in this study are showed in the Table 2.…”
Section: Microbiological Analysis and Biochemical Activitymentioning
confidence: 99%
“…About two-stage AD process, most of researchers have been focused on the optimization of gas production (GP), removal organic matter and process optimization but very few reports discussed in detail the microbial population dynamics involved during different stages of the thermophilic anaerobic co-digestion of WAS and OFMSW for hydrogen production. Molecular tools like the fluorescence in situ hybridization (FISH), based on sequence comparison of small-subunit ribosomal RNA (rRNA) molecules, can detect specific whole cells/organisms in biological samples (Crocetti et al, 2006;Ariesyady et al, 2007;Montero et al, 2009;Zahedi et al, 2013aZahedi et al, , 2013bZahedi et al, , 2014aZahedi et al, , 2014b.…”
Section: Introductionmentioning
confidence: 99%